Relationship between addiction severity of alcohol-substance users and co-dependency levels of family members - Kaplan, Özgen; Özbaran, Nazlı Burcu (Journal of Dependence, 2024)
Objective: The aim of this study was to evaluate the relationship between addiction severity of individuals with alcohol substance use disorder and co-dependency levels of their family members.Method: The study was conducted with 122 people aged 18 years and older, diagnosed with alcohol substance use disorder, and their family members. Data were collected at Green Crescent Counseling Centers, that provide free outpatient psychosocial support. The participants were administered the case report form, Addiction Profile Index Scale (BAPI) and Co-Dependency in Substance Use Disorder Scale (CODSUDS).Results: Of the 122 participants, 94.3% were male and 5.7% were female. When the dependency severity of the participants was analyzed, 41.8% were high, 33.6% were moderate and 24.6% were low. According to this analysis, a statistically significant positive correlation was found between the total score of the CODSUDS score, which measures the level of co-dependency of families, and the BAPI Total (r=0.320 p
Keywords: Addiction; alcohol use disorder; sustance use disorder; codependency